The Role of Faith in Maintaining the Mental Health of Muslim Students in Middle Life Demands and Social Comparative Culture: A Phenomenological Study of Students at the University of Muhammadiyah Indonesia (UNISMA Bekasi) - Akmal Rizki Gunawan Hsb; Astia Salsabil; M. Yoga Chossy Pratama (Journal of Economics, Management, Development, and Education, 2026)
University students' mental health is influenced by academic demands, family responsibilities, and a culture of social comparison, all of which may contribute to psychological distress. From an Islamic perspective, faith (iman) is regarded as an important factor that helps individuals cope with life's challenges. This study aimed to explore the role of faith in maintaining the mental health of Muslim university students amidst life demands and social comparison. This study employed a qualitative approach using a phenomenological method. The participants consisted of one primary participant, a Muslim student at Universitas Muhammadiyah Indonesia (UNISMA Bekasi) who met the research criteria, and one significant other who served as a supporting source of information. Data were collected through semi-structured in-depth interviews and analyzed using thematic analysis with source triangulation to enhance the credibility of the findings. The results identified six major themes: (1) university life demands as a source of pressure, (2) the psychological impact of life demands, (3) experiences of social comparison and their psychological impact, (4) strategies for coping with life stress, (5) faith as a religious coping mechanism, and (6) the meaning of faith as the foundation of mental health. The findings indicate that faith functions as a protective factor by helping participants reduce anxiety, attain inner peace, regulate emotions, develop more positive perspectives toward life's challenges, and strengthen their ability to cope with stress. Therefore, faith serves not only as a spiritual dimension but also as an essential foundation for maintaining the mental health of Muslim university students amidst life demands and a culture of social comparison